The effect of complex exercises according to playing positions in developing some physical abilities of football players aged) 16-18(years - Saleem, Mohammed; Rashid, Ammar (Journal of Physical Education, 2025)
Research objective: To determine the extent of the impact of vehicle exercises on playing positions in developing some talents for football players aged (16-18) years. The research assumed: that there were statistically significant differences between the results of the pre- and post-tests in physical abilities according to playing positions for football players aged (16-18) years, in favor of the experimental group. The researchers used the experimental method (by designing two experimental groups and a control group with pre- and post-tests for its suitability and the nature of the problem, to achieve the research objectives). The community of origin (216) was deliberately identified, represented by Kirkuk Governorate football club players aged (16-18 years) who represent (10) clubs. The number of members of the research community was (26) players. The research sample was randomly divided into two groups, one experimental and the other a control, with (10) players for each group. A number of players were chosen from the research sample to conduct the exploratory experiment, numbering (6) players. The research sample numbered (20) players, with a percentage of (12.03%) of the total research community. The research sample was chosen intentionally, represented by North Gas Sports Club players aged (16-18) years, and the exploratory experiment was conducted on Tuesday, September 19/9/ 2023, at (five-thirty in the afternoon) at the North Gas Sports Club stadium. Football on a group of players in the basic research sample, which numbered (6) players. The researchers concluded: that complex exercises according to playing positions have an impact in developing the physical abilities of football players aged (16-18) years, the most important recommendations. The necessity of using complex exercises according to playing positions in developing the physical capabilities of football players aged (16-18) years by coaches working in clubs and national teams.